High-precision adaptive temperature control performance of thin positive temperature coefficient materials with ultra-high resistance-temperature coefficient - Yang, Yin-Fa; Hao, Jian-Min; Zhang, Wei; Shen, Yi-Tao; Zhou, Rui; Chen, Hua; Cheng, Wen-Long (Applied thermal engineering, 2024)
•A material with high resistance temperature coefficient was prepared.•The prepared material has excellent thermal cycling stability.•The lightweight design of the temperature control system is realized.•The prepared materials can achieve high-precision temperature control. Positive temperature coefficient (PTC) material with high resistance-temperature coefficient has excellent adaptive temperature control performance. In this paper, a positive temperature coefficient material with a high resistance-temperature coefficient (2.8/°C) was prepared, and it still had excellent PTC characteristics after multiple thermal cycles, which greatly compensated for the low resistance-temperature coefficient and poor thermal cycling of previous polymer-based PTC materials. The adaptive temperature control performance of the heating system composed of PTC materials was studied experimentally, PTC materials exhibit excellent self-adaptive temperature control performance at different ambient temperatures. In order to further study the adaptive temperature control performance of heating system, the corresponding theoretical model is established and the accuracy of the model is verified by experiments. The simulation results show that when the ambient temperature changes sinusoidally with different periods or different amplitudes, the temperature control system can well weaken the influence of the change of the ambient temperature on the controlled object. In addition, when the weather data (including temperature and wind speed) of three different cities within a day are selected as the operating conditions of the temperature control system, the maximum temperature difference of the controlled object throughout the day is only 2.7 °C. The results show that PTC materials with high resistance-temperature coefficient have excellent self-adaptive temperature control performance.